Association of GSTM1 and GSTT1 genetic polymorphism with blood methylmercury level and birth outcome among fish-eating urban pregnant women - Abedinlah, Amirah (2020)
Methylmercury (MeHg) is the most toxic mercury species widely found in marine fish and is exposed to human through fish consumption. The exposure to MeHg during pregnancy has been associated with having significant effects on the central nervous system of developing fetus. MeHg might even affect the health of the newborns at the seemingly non-detrimental environmental exposure level. Marine fish consumption is known to be the main contributor to non-occupational MeHg exposure among the general population. MeHg elimination in human is related to the glutathione (GSH) detoxification system, in a bile mediated mechanism through the conjugation of Glutathione S transferase (GST) that transforms MeHg into stable form and eliminates through faeces. Both glutathione-S-transferase- mu 1 (GSTM1) and glutathione-S-transferase- theta 1 (GSTT1) genes are polymorphic in the human population, and the absences of these genes resulted in the loss of functional activity, thus leading to the increase of MeHg level in the body. Therefore, this prospective cohort study based in a Petaling district urban area of Selangor, was conducted to determine the maternal blood MeHg concentration level, to evaluate the association between the MeHg level to the GSTM1 and GSTT1 genes polymorphisms, to determine the frequency of marine fish consumption, and to obtain the birth outcome among the respondents. Pregnant women from the first trimester until the third trimester aged between 20 to 49 years old (N=215) who consumed marine fish participated in this survey and were included in the screening, interview, and blood sample collection processes. Five (5) mL of venous blood was sampled from each respondent and analyzed for the MeHg concentration by using liquid chromatography coupled with inductively coupled plasma mass spectrometry (LCICP- MS). The genotyping of GSTM1 and GSTT1 genes was performed using the polymerase chain reaction (PCR) method. Statistical analyses were performed using IBM SPSS to determine the maternal blood MeHg concentration, GSTM1 and GSTT1 genes polymorphism, the frequency of marine fish intake and the predictors of maternal blood MeHg concentration. The analysis showed that the median of MeHg in maternal blood was 1.70 ug/L, 11.2% higher than the guideline limit of 3.5 ug/L Hg. The concentration of MeHg in the respondents ranged from 0.11 to 9.90 ug/L. The prevalence of GSTM1 null and GSTT1 null were 69% and 38%, respectively. For the combination genotypes of GSTM1-/GSTT1+, GSTM1+/GSTT1- , GSTM1-/GSTT1- and GSTM1+/GSTT1+, the frequency were 43%, 11%, 27% and 20%, respectively. The Chi-Squared ( 2) test showed that there was no significant association between the GSTM1 null and GSTT1 null polymorphism with the maternal blood MeHg concentration of respondents (p = 0.088 and p= 0.077, respectively). However, those with the GSTM1+/GSTT1- genotype showed significant association with higher maternal blood MeHg concentration, as compared to other genotypes (AOR= 5.469, 95% CI = 2.03 - 14.73). The most significant contributor to the maternal blood MeHg was the GSTM1+/GSTT1- genotype (AOR=7.361, 95% CI = 1.68 - 32.16). The finding also shows that there was no association between the maternal blood MeHg concentration with the birth outcome. In conclusion, there appeared to be no evidence of an effect of fish consumption on maternal blood MeHg levels as well as no evidence of MeHg levels to birth outcome, however, there is a possibility of maternal blood MeHg exposure risk among those with GSTT1 null genotype, as they may tend to retain MeHg in the body.